Shape‐Designable Polyhedral Liquid Marbles/Plasticines Stabilized with Polymer Plates. Issue 24 (4th November 2020) - Fujiwara, Junya; Geyer, Florian; Butt, Hans‐Jürgen; Hirai, Tomoyasu; Nakamura, Yoshinobu; Fujii, Syuji
Abstract: Polyhedral liquid marbles/plasticines are prepared using (sub)millimeter‐sized polymer plates as a stabilizer and water as an inner liquid. Precise control of size and shape can be successfully performed by tuning the size ratio of the water droplet and the plate, number of plates adsorbed to the droplet, coalescence (jointing) of multiple polyhedral liquid marbles/plasticines, and application of external mechanical stress. Thanks to interfacial jamming of the plates, plastic deformation of the liquid marbles/plasticines is achieved. The authors are able to fabricate liquid marbles/plasticines with various shapes including A–Z letters of alphabet. Liquid marble/plasticine with an aspect ratio exceeding 800, the largest aspect ratio ever reported, is also successfully prepared; the length of the liquid marble/plasticine exceeded 1.5 m. The liquid marbles can be picked up and be piled up on top of each other using tweezers or fingers. Furthermore, Janus‐type liquid marbles/plasticines with different curvatures and different stabilizers in a single liquid marble/plasticine can be fabricated by coalescence (jointing) of near‐spherical and cuboid liquid marbles/plasticines stabilized by plates with different sizes. An internal liquid flow from the near‐spherical liquid marble to the cuboid liquid marble/plasticine immediately after jointing is observed, making this system act as a micropump. Abstract : Liquid marbles/plasticines whose shape and size can be precisely controlled are introduced. Thanks to interfacial jamming of the particles, the liquid marbles/plasticines with various shapes including A–Z letters of alphabet and sizes from 2 mm to >1.5 m can be fabricated. Furthermore, Janus‐type liquid marbles/plasticines with different curvatures and different stabilizers in a single liquid marble/plasticine are successfully fabricated.